Naturally ventilated colonial school classrooms in Malaysia are conducive to learning environment - Sanusi, Aliyah Nur Zafirah; Azmin, Aida Kesuma; Abdullah, Fadzidah; Kassim, Mohd Hisyammudin (2016)
The study is intended to evaluate the comfort level of learning environment in three naturally ventilated colonial schools in Malaysia through the voice of students aged between 13 and 17. This study focuses on the influence of the colonial school classroom physical environment towards the students' comfort and behaviour. The research has two objectives: To evaluate post-occupancy comfort level and behavior in the naturally ventilated colonial schools and to suggest design elements that could improve the comfort level of a school classroom. Observations and investigations were conducted in three colonial schools; Victoria Institution, Methodist Girls Secondary School and Maxwell Secondary School in the morning session, between 7:45a.m. and 1:00p.m.. Survey questionnaires were distributed to one classroom of each school and simultaneously, an inventory of each classroom physical environment were recorded. It was found that the observed classroom differs slightly in the window-to-wall ratio, window size and occupancy density, which have impact on the indoor environment and students' comfort and behaviour. From the survey results, among the three schools, the students in Methodist Girls Secondary School are mostly comfortable throughout the morning session. In conclusion, several design elements, which can be adopted from the architecture of colonial period, that makes them conducive to learning environment are window-to-wall ratio, window sizes and occupancy density.